1997
DOI: 10.1080/13636829700200023
|View full text |Cite
|
Sign up to set email alerts
|

Teaching information technology to the ‘computer shy’: a theoretical perspective on a practical problem

Abstract: In both post-compulsory education and training there is a growing need for every student, teacher and employee to have at least a basic level of computer competence. It is therefore necessary to consider the needs of the 'computer shy', i.e. those individuals who have up until now avoided coming into contact with computers and are reluctant to take part in computer training. This article begins by examining the psychological, sociological and operational origins of an individual's computer reticence and anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…It could be argued that the reason for the low use of EMRK by pre-service teachers in this study was the fact that the technology itself may have been a barrier to its use. In a review of previous studies on why people are anxious in their adoption of new technologies, Selwyn (1997) indicated that there may be psychological, sociological or operational factors behind an individual's reticence in using ICT. Interestingly however, when pre-service teachers were asked to report on their success rate for recording classroom data using traditional methods that did not involve the use of technology (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…It could be argued that the reason for the low use of EMRK by pre-service teachers in this study was the fact that the technology itself may have been a barrier to its use. In a review of previous studies on why people are anxious in their adoption of new technologies, Selwyn (1997) indicated that there may be psychological, sociological or operational factors behind an individual's reticence in using ICT. Interestingly however, when pre-service teachers were asked to report on their success rate for recording classroom data using traditional methods that did not involve the use of technology (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in a review of previous studies of computer anxiety, or what may be called digital divide was conducted by Selwyn (1997) cited in Preston, Cox & Cox (1999), found that a major deterrent to the use of computers by teachers was computer phobia. These teacher anxieties could be caused by:…”
Section: Digital Divide In Educationmentioning
confidence: 99%
“…However, most students claimed that they do not learn IT skills through their academic studies. They learn by trial and error, and rely mostly on peer support, especially those who consider themselves computer shy (Davis, 1999;McEuen, 2001;Selwyn, 1997).…”
Section: Literature Review On Students' It Skills and Employabilitymentioning
confidence: 99%